Building laboratory capacity to support HIV care in Nigeria: Harvard/APIN PEPFAR, 2004-2012 - Donald J. Hamel; Jean-Louis Sankalé; Jay O. Samuels; Abdoulaye D. Sarr; Beth Chaplin; Eke Ofuche; Seema T. Meloni; Prosper Okonkwo; Phyllis J. Kanki (AOSIS, 2015)
Introduction: From 2004-2012, the Harvard/AIDS Prevention Initiative in Nigeria, funded through the US President's Emergency Plan for AIDS Relief programme, scaled up HIV care and treatment services in Nigeria. We describe the methodologies and collaborative processes developed to improve laboratory capacity significantly in a resource-limited setting. These methods were implemented at 35 clinic and laboratory locations. Methods: Systems were established and modified to optimise numerous laboratory processes. These included strategies for clinic selection and management, equipment and reagent procurement, supply chains, laboratory renovations, equipment maintenance, electronic data management, quality development programmes and trainings. Results: Over the eight-year programme, laboratories supported 160 000 patients receiving HIV care in Nigeria, delivering over 2.5 million test results, including regular viral load quantitation. External quality assurance systems were established for CD4+ cell count enumeration, blood chemistries and viral load monitoring. Laboratory equipment platforms were improved and standardised and use of point-of-care analysers was expanded. Laboratory training workshops supported laboratories toward increasing staff skills and improving overall quality. Participation in a World Health Organisation-led African laboratory quality improvement system resulted in significant gains in quality measures at five laboratories. Conclusions: Targeted implementation of laboratory development processes, during simultaneous scale-up of HIV treatment programmes in a resource-limited setting, can elicit meaningful gains in laboratory quality and capacity. Systems to improve the physical laboratory environment, develop laboratory staff, create improvements to reduce costs and increase quality are available for future health and laboratory strengthening programmes. We hope that the strategies employed may inform and encourage the development of other laboratories in resource-limited settings.